The Solanum commersonii Genome Sequence Provides Insights into Adaptation to Stress Conditions and Genome Evolution of Wild Potato Relatives. Issue 4 (14th April 2015) - Aversano, Riccardo; Contaldi, Felice; Ercolano, Maria Raffaella; Grosso, Valentina; Iorizzo, Massimo; Tatino, Filippo; Xumerle, Luciano; Dal Molin, Alessandra; Avanzato, Carla; Ferrarini, Alberto; Delledonne, Massimo; Sanseverino, Walter; et al.
Abstract : The draft genome and transcriptome sequences of the wild potato species S. commersonii demonstrate the usefulness of genome sequences from wild relatives for elucidating evolutionary mechanisms contributing to Solanum species diversity and understanding changes in response to cold. Abstract: Here, we report the draft genome sequence of Solanum commersonii, which consists of ∼830 megabases with an N50 of 44, 303 bp anchored to 12 chromosomes, using the potato ( Solanum tuberosum ) genome sequence as a reference. Compared with potato, S. commersonii shows a striking reduction in heterozygosity (1.5% versus 53 to 59%), and differences in genome sizes were mainly due to variations in intergenic sequence length. Gene annotation by ab initio prediction supported by RNA-seq data produced a catalog of 1703 predicted microRNAs, 18, 882 long noncoding RNAs of which 20% are shown to target cold-responsive genes, and 39, 290 protein-coding genes with a significant repertoire of nonredundant nucleotide binding site-encoding genes and 126 cold-related genes that are lacking in S. tuberosum . Phylogenetic analyses indicate that domesticated potato and S. commersonii lineages diverged ∼2.3 million years ago. Three duplication periods corresponding to genome enrichment for particular gene families related to response to salt stress, water transport, growth, and defense response were discovered. The draft genome sequence of S. commersonii substantially increases our understanding of the domesticated germplasm, facilitating translation of acquired knowledge into advances in crop stability in light of global climate and environmental changes.